Pendampingan Manajemen Keuangan Dan Analisis Kelayakan Usaha Greenhouse Hidroponik Di Pesantren Suryalaya Tasikmalaya - Sani Haryati; Akhmad Hidayat Nurul Akbar (CV. SINAR HOWUHOWU, 2026)
This community service activity focuses on financial management mentoring and business feasibility analysis for the hydroponic greenhouse enterprise at Pesantren Suryalaya, Tasikmalaya. The approach used was participatory mentoring, in which the team worked directly with greenhouse managers to review and analyze the financial records of the first production cycle. The mentoring process covered cost structure analysis, cost of goods sold (COGS/HPP) calculation, investment amortization, and marketing channel evaluation. The analysis revealed that the cost structure in the first cycle was dominated by one-time infrastructure investment, while recurring operational costs per cycle were relatively manageable. Managers were assisted in understanding that profitability in subsequent cycles is highly dependent on operational cost efficiency and pricing strategy improvements. As an output, participants were able to prepare a structured financial report and understand the financial position of their enterprise more clearly. This activity contributes to strengthening financial management practices and the long-term sustainability of the pesantren-based hydroponic business.